Genetic diversity of eucalypts for germplasm conservation in Forest Area with the Special Purpose of Mount Bromo, Karanganyar, Indonesia (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Rahayu, Fatimah, Wiwoho J, Firdaus SU, Pujiyono, Marimin, Arianto DP, Pramono A. 2021. Genetic diversity of eucalypts for germplasm conservation in Forest Area with the Special Purpose of Mount Bromo, Karanganyar, Indonesia. Biodiversitas 22: 4223-4235. As a repository of a gene pool, eucalypts germplasm enriches biodiversity, maintains ecosystem sustainability, and aids in conservation. Therefore, this study aims to analyze the genetic diversity of eucalypts (Corymbia and Eucalyptus) for the development of germplasm conservation in Forest Area with the Special Purpose (KHDTK) Bromo Forest, Karanganyar, Indonesia. In this study, 14 simple sequence repeat (SSR) markers were used to assess the genetic diversity among 20 accessions (Corymbia and 5 Eucalyptus species) from Central and West Java. Subsequently, the genetic parameters were measured and a phylogenetic tree was constructed. The result showed that the SSR markers have high variability, although they belong to different genera. Furthermore, the genetic diversity showed 49 alleles with an average of 3 alleles per locus, while the polymorphism information content (PIC) values were 0.55. There were 4 SSR markers (EMBRA13, EMBRA8, EMCRC11, and EMBRA2) with high PIC value, while the gene diversity (He) of Corymbia and 5 Eucalyptus showed a low level of genetic diversity. The genetic relationship and population structure were divided into genera Corymbia and Eucalyptus. For further application, the eucalypt cultivated in the KHDTK Bromo Forest can contribute as a reference set and 14 SSR markers as a potential marker in combination with morphological characterization to generate a database for germplasm management and conservation.
Keywords: Genetic relationship, Kawasan Hutan Dengan Tujuan Khusus (KHDTK), Simple Sequence Repeat